Local Climatological Data Summary: Anna, Illinois, 1901-1989 - Bryan, Audrey A.; Armstrong, Wayne (Illinois State Water Survey, 1990)
Anna (Union County) has a temperate continental climate, dominated by maritime tropical air from the Gulf of Mexico from about March through November. Gulf air generally supports relative humidities of about 60% during the day and 85% at night. During these months, there are occasional, brief interruptions of drier, cooler air from the Pacific Ocean, but typically only last for a few days. From November through March, the Anna area is dominated by Pacific Ocean air. Three or four times each winter, cold, dry air from the Canadian Arctic breaks south, bringing temperatures into the teens and even units. Average annual precipitation is about 45 inches, the highest for the state. is peer reviewed Submitted by Agnes Stankiewicz (stankie2@illinois.edu) on 2014-10-29T15:45:28Z No. of bitstreams: 1 ISWSMP-98-2.pdf: 967199 bytes, checksum: c3433aea1623bb33874b89cd5e30f76e (MD5) Made available in DSpace on 2014-10-29T15:45:29Z (GMT). No. of bitstreams: 1 ISWSMP-98-2.pdf: 967199 bytes, checksum: c3433aea1623bb33874b89cd5e30f76e (MD5) Previous issue date: 1990 published or submitted for publication Open